Análise e projeto do conversor Boost-Quadrático-Buck associado à célula de comutação quase ressonante Single-Switch - Silva, Welker Gomes (2013)
This paper presents the implementation of a Boost-Quadratic-Buck CC-DC converter associated with a single-switch quasi-resonant switching cell. The proposed converter operates with an active switch and can be powered by a wide range of direct current input voltage. This feature allows the converter to be powered by a battery system. Experimental results extracted from a prototype are presented.